New Black cyclones : racism, representation and revolutions of power in cycling / Marlon Lee Moncrieffe. - Moncrieffe, Marlon Lee (Bloomsbury Sport, 2024)
Ex-international cyclist Marlon Lee Moncrieffe examines how the cycling industry is tackling racism within the sport today. By interviewing key players in professional cycling, he considers its present and future in light of the Black Lives Matter protests. Gathering evidence and interviews from across the cycling spectrum - including British Cycling and professional bodies in the US, Europe and the African continent - the book features the voices of elite and professional riders, commentators, grassroots riders and activists.